Assessing informed consent practices during normal vaginal delivery and immediate postpartum care in tertiary-level hospitals of Bangladesh - Karim, Md Abdul; Ahmed, Syed Imran; Ferdous, Jannatul; Islam, Bushra Zarin; Tegegne, Henok Ayalew; Aktar, Bachera (European Journal of Midwifery, 2022)
This article was published in the European Journal of Midwifery [© 2019 Karim M.A. This is an Open Access article distributed under the terms of the Creative Commons Attribution Non Commercial 4.0 International License. (http://creativecommons.org/licenses/by-nc/4.0)] and the definite version is available at: https://doi.org/10.18332/ejm/109311 The Journal's website is at: http://www.europeanjournalofmidwifery.eu/Assessing-Informed-Consent-Practices-During-Normal-Vaginal-Delivery-Process-and-Immediate,109311,0,2.html